Viewpoint: Engagement in local social-ecological knowledge practices in a seasonal cycles approach for transitioning to future sustainability - Rob O'Donoghue (Environmental Association of Southern Africa, 2019)
This paper explores climate as variable natural forces driving seasonal cycles1 that many African cultures had adjusted themselves to within intergenerational knowledge practices of longue durée. The study points to the need to re-orientate and expand climate science education so that it is centred on the seasonal cycles and intergenerational learning to better align transitioning to future sustainability with these in our southern African contexts of climate change today. The narrative touches upon historical accounts of knowledge practices amongst the Krobo, Bemba, Shona, Zulu and Xhosa, briefly pointing to how each, as an African culture, is situated as a social-ecological entity within the climatic tapestries of our African landscapes. It takes note of how cultural articulation within the seasonal cycles of regional climate have a long history with adaptive change in some contexts in more recent times. The review suggests that our learning in relation to emerging climate change should be informed by these histories of intergenerational knowledge practice. It notes how a better grasp of these could be important drivers of a widening cultural response to the changing dynamics in our climatic surroundings today. The brief study suggests that southern Africa is a special place with many unique and interesting climatic processes and associated socio-ecological systems and practices. These can provide engaging perspectives for informing education to mitigate or adapt to climate change. Here, a situated exploration of seasonal cycles can draw on both the latest in modern climate science and the rich social-ecological heritage of Africa briefly touched upon in the study. A model of process is offered for how both can be used in a seasonal cycles approach climate change education. This better situated and more inclusive approach can enable us to contemplate how we might best adjust our social-ecological dispositions and practices in the changing world that we all share.